Targeting the major pro-inflammatory interleukin-6-type cytokine receptor gp130 by antagonistic single domain antibodies - Pudewell, Silke; Heuser, Julia; Dorogobed, Inna; Lipinski, Britta; Tran, Thi Hong Hue; Metzenmacher, Pia; Kunze, Richard; Geyer, Felix; Zielonka, Stefan; Floss, Doreen M.; Kolmar, Harald; Moll, Jens M.; et al. (Frontiers in Immunology, 2025)
IntroductionAlthough Interleukin (IL)-6-type cytokine signaling is critical for maintaining the body's homeostasis, aberrant signaling has been observed in numerous diseases including autoimmunity and cancer. Currently, all approved biologics that inhibit IL-6-type cytokines specifically target the key pro-inflammatory mediator IL-6 or its receptor (IL6R). Historically, direct inhibition of glycoprotein 130 (gp130)—the shared transmembrane receptor for IL-6-type cytokines—was avoided due to concerns that broad suppression might cause more harm than benefit. However, this view is being reconsidered in light of the clinical success of Janus kinase (JAK) inhibitors, which broadly disrupt cytokine signaling, including pathways mediated by gp130.MethodsHere we developed four single domain antibodies (sdAb), consisting out of a camelid-derived nanobody and a human Fc-fragment, and characterized them by direct protein interaction analysis, epitope binding, epitope binning, as well as inhibition of cytokine-induced stimulation and proliferation of appropriate Ba/F3 cell lines and trans-migration in HT-29 cells.ResultsThe four sdAb-Fc constructs GP01-, GP11- GP13- and GP20-Fc bind directly to gp130 in the cytokine binding module (CBM) and largely inhibit IL-6-type cytokine signaling by interfering with the high-affinity binding site of IL-6, IL-11, CLCF1, CT1, CNTF, OSM and LIF. Furthermore, we functionally demonstrate the inhibitory effect of the selected nanobodies in cell-based transmigration assays of the human colorectal cancer cell line HT-29.DiscussionIn summary, our study has identified and characterized four novel inhibitory high-affinity gp130 nanobodies with potential for use in cytokine-dependent autoimmunity or cancer therapy.